Advancing relugolix analysis: A comparative study and AQbD-driven method optimization with stability testing - Priyanka Nagar,, Arvind Kumar Sharma, Robin Kumar, Chhaya Chauhan, Rini Singhal, Minakshi Garg (Journal of Applied Pharmaceutical Science, 2025)
The current study aimed to develop a novel liquid chromatographic method based on analytical quality by design to analyze relugolix and its related substances. This study builds upon a comparative review of existing analytical methods, highlighting the absence of a pharmacopoeial standard for relugolix determination. To address this gap, a new method was designed and validated. Method development began with preliminary studies to identify critical method attributes and parameters influencing the analytical process. Design of experiments was employed, using a full factorial design for initial screening, while method optimization was carried out through the central composite design approach. The pH and column temperature were identified as critical parameters, whereas the tailing factor and resolution between relugolix and its amine impurity were key performance attributes. The study adhered to the International Council for Harmonization of Technical Requirements for Pharmaceuticals for Human Use Q2 guidelines, ensuring the method’s reliability for routine pharmaceutical analysis. Additionally, stability-indicating degradation studies were conducted under various stress conditions, with degraded samples analyzed using infrared spectroscopy, liquid chromatography–mass spectrometry, and nuclear magnetic resonance techniques. The developed liquid chromatographic method provides valuable insights into the quality and chemical stability of relugolix and its related substances, supporting the further development and regulatory assessment of the drug.
Keywords: Relugolix, AQbD, method development and validation, HPLC, related substances